Receptor Status Differences in Prognosis for Breast Cancer - Yelda Deligöz Bildacı; Deniz Yamaç; Uğur Coşkun (Gazi Medical Journal)
Objective: Breast cancer is a type of cancer that originates in breast tissue cells. It is the most common cancer type in the world after lung cancer. The prognosis of the disease mostly depends on the type and stage of cancer. One of the worst prognoses is seen in a specific type called Triple-negative breast cancer (TNBC), which represents not having any of the three most recognized receptors, namely estrogen, progesterone, and c-erb2 receptors. Our objective was to determine the difference in overall and disease-free survival for breast cancer types categorized by receptor status. Methods: This is a retrospective matched case-control study with breast cancer patients of two types. A total of 102 patients were divided equally into having TNBC of 51 patients in one arm and triple-positive breast cancer (TPBC) of 51 patients in the other arm. Analyses were run for disease prognostic values and patients’ demographic values. Results: Disease free survival were 63±10.6 months and 93.2±4.9 months in the fifth year for the TNBC and TPBC groups, respectively. (p=0.004) Overall survival was significantly different as 73.9±7.3 months for TNBC and 97.7±2.3 months for TPBC (p=0.002). Conclusion: TNBC prognosis is worse than that of other breast cancer types. The most important reason is being unable to use hormonal treatment because of the receptor status, and a disease-specific targeted treatment could not have been developed so far. Therefore, it is necessary to identify new molecular targets and develop treatments for them.